2016
DOI: 10.4329/wjr.v8.i4.390
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of intra-procedural cone-beam computed tomography in modified balloon-occluded retrograde transvenous obliteration of gastric varices

Abstract: AIM:To evaluate whether intra-procedural conebeam computed tomography (CBCT) performed during modified balloon-occluded retrograde transvenous obliteration (mBRTO) can accurately determine technical success of complete variceal obliteration. METHODS:From June 2012 to December 2014, 15 patients who received CBCT during mBRTO for treatment of portal hypertensive gastric variceal bleeding were retrospectively evaluated. Three-dimensional (3D) CBCT images were performed and evaluated prior to the end of the proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…For BRTO, PARTO, and CARTO, clinical success ranges from 91 to 100%, 90.6 to 100%, and 100%, respectively. 2,4,24,[27][28][29]31,38,39 Kim et al detected similar clinical success rates (defined as lack of variceal enhancement on postprocedural CT and cessation of bleeding on endoscopy) between BRTO with EO (93.9%) or STS (92%) and PARTO with Gelfoam (100%). 31 Acutely bleeding gastric varices carry a high mortality with limited treatment options.…”
Section: Clinical Success and Survivalmentioning
confidence: 83%
See 1 more Smart Citation
“…For BRTO, PARTO, and CARTO, clinical success ranges from 91 to 100%, 90.6 to 100%, and 100%, respectively. 2,4,24,[27][28][29]31,38,39 Kim et al detected similar clinical success rates (defined as lack of variceal enhancement on postprocedural CT and cessation of bleeding on endoscopy) between BRTO with EO (93.9%) or STS (92%) and PARTO with Gelfoam (100%). 31 Acutely bleeding gastric varices carry a high mortality with limited treatment options.…”
Section: Clinical Success and Survivalmentioning
confidence: 83%
“…11 The use of cone beam CT can aid in evaluating this embolization end point. 24 The balloon remains inflated for 4 to 24 hours while the patient is immobilized in the ICU, followed by return to the angiography suite for balloon deflation. 11,20,23 An accelerated BRTO technique can be used in small gastrorenal shunts (<15 mm), in which traditional BRTO is followed by terminal Gelfoam plug or coil deployment, through the occlusion balloon, eliminating the need for prolonged balloon inflation.…”
Section: Balloon-occluded Retrograde Transvenous Obliterationmentioning
confidence: 99%
“…The mean fluoroscopic time was 27 minutes and ranged from 13 minutes to 47 minutes. The reported technical success rates of BRTO and modified BRTO ranged from 79.6% to 100% ( 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 24 26 ). We believe this technical success can be further improved using an intra-procedural CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this technical success can be further improved using an intra-procedural CBCT. The utility of the CBCT in conventional and modified BRTO has been described in several studies ( 20 21 22 23 24 ). In these studies, investigators concluded that CBCT can provide enough information to either terminate or continue the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation